From Macro to Micro: A Summary of Dr. Angel Lin's Research over Time - Haiyi Yan (Canadian Society for Studies in Education, 2024)
This article provides a comprehensive overview of  Lin's scholarly contributions, spanning various periods from her early research endeavors in Hong Kong to her recent work in Canada. Employing a chronological approach, it delves into the distinct phases of Lin's research trajectory, examining how her scholarship has evolved over time. By contextualizing her work within the socio-cultural milieu of each respective period, the article offers insights into the interconnectedness between Lin's research interests and the prevailing social conditions. Through this analysis, readers gain a deeper understanding of the multifaceted dimensions of Lin's academic pursuits and their broader implications within the field of study.